INTERNALIZATION OF THE VALUE OF KEMARSUDIRINIAN BROTHERHOOD WITH THE UNIVERSE: IN THE PROJECT OF STRENGTHENING PANCASILA STUDENT’S PROFILE - Nanik Tri Wiyanti; Nita Priyanti (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
Character values are an important basic thing in education to create a golden generation, this research is the teacher as a guide to internalize the values of the Marsudirinian brothers and sisters with the universe. Marsudirini provides services by instilling Christian values in a spirit of brotherhood which have vision and mission that lead children to become intelligent individuals wholly and in balance This study aims to find out the project of strengthening the Profil Pelajar Pancasila. Pancasila Students exemplify a variety of traits and skills that should be attained and are founded on Pancasila's high ideals. This research uses descriptive qualitative methods, with data collection techniques in the form of questionnaires, interviews and documentation. The goal of the qualitative research approach is to gain a comprehensive overall picture of the subject being studied by using methods, steps, and procedures that involve more data and information from respondents as subjects who may express their own answers and feelings. In the internalization process it will focus on the dimensions of love for the universe and God's creation, with 10 questionnaire indicators as an assessment aspect of 30 children, an overall assessment aspect of 59% BSH (Developing According to Expectations) is obtained, this value is obtained based on the results of a teacher survey in seeing the influence of a child's independence to carry out activities according to the listed indicators. Supported by the results of interviews from the three informants, namely parents, principals, and homeroom teachers, the impact of positive changes on internalization is instilled in children and adds to the value of attitude and moral behavior.